Spatial variations of PM2.5-bound parent, nitrated, and oxygenated PAHs at urban and suburban sites in the Ili River Valley: Characteristics, sources, and health risks - Zhao, Xueyan; Ji, Yaqin; Bai, Wenyu; Guo, Liyao; Gu, Chao; Liang, Handong; Li, Xianqing; Yang, Wen (Journal of environmental sciences (China), 2025)
Polycyclic Aromatic Hydrocarbons (PAHs), along with their derivatives nitro-PAHs and oxy-PAHs, are globally recognized toxic pollutants. This research conducted daily PM2.5 sampling in winter 2021 at three urban (YNCE, SWP, and NG) and three suburban sites (HC, CTV, and YNE) in the Ili River Valley (IRV). For the first time in the IRV, a comprehensive study on 39 PAHs and derivatives was carried out. The results showed that the average ∑PAHs concentration was 130.21 ± 98.94 ng/m3, with ∑16PAHs constituting the dominant fraction (112.51 ± 86.48 ng/m3). The mean BaP and the total BaP equivalent quotient (TEQ) concentrations were 10.28 ± 8.85 ng/m3 and 19.74 ± 16.70 ng/m3, respectively. Approximately 88 % of the daily BaP averages and 98 % of the daily TEQ averages exceeded the national daily average standard of BaP (2.5 ng/m3), indicating severe local BaP pollution. Urban sites had notably higher ∑PAHs and TEQ concentrations than suburban sites, attributed to increased vehicular traffic and coal combustion in urban areas. PMF results showed that traffic emissions (32.7 %–60.5 %), coal combustion (13.9 %–24.3 %) and secondary formation (14.7 %–22.7 %) were the primary contributors to ∑PAHs. Urban sites experienced a greater influence from traffic, while suburban sites were more impacted by coal and biomass burning. On polluted days, traffic sources' contributions increased significantly at HC, YNE, NG and YNCE sites, and secondary formation sources' contributions grew at CTV and YNCE sites. The source-dependent BaPeq results underscored the role of secondary-formed PAH derivatives in TEQ. Enhanced secondary reactions in winter were facilitated by high NO2 and O3 levels, relative humidity (RH), and elevated temperatures (T). The findings of this study provide valuable insights for devising emission control strategies to safeguard both the environment and human health in the IRV.